Pengaruh Pembiayaan Mudharabah Dan Pembiayaan Musyarakah Terhadap Return On Asset (ROA) Pada Bank Muamalat Indonesia Periode 2016-2023 - Ilmiyah, Syarofatul; Purnamasari, Diana Nur Indah (Jurnal Perbankan Syariah, 2024)
This research aims to analyze the impact of mudharabah and musyarakah financing on Return On Asset (ROA) at Bank Muamalat Indonesia during the 2016-2023 period. Employing a quantitative approach with secondary data and an associative research method, the study utilizes purposive sampling techniques and data analysis through classical assumption tests, multiple linear regression, and hypothesis testing with the aid of SPSS version 24. The research findings indicate that mudharabah and musyarakah financing, individually, do not significantly influence ROA, with significance levels of 0.712 and 0.067, respectively, and t-statistic values lower than the t-table. However, simultaneously, mudharabah and musyarakah financing have a significant impact on ROA, as evidenced by the significant F value (0.008 < 0.05) and an F-statistic exceeding the F-table (8.203 > 3.328).